THE SYNTACTIC AND STYLISTIC FEATURES OF ARMENIAN NOTARY DOCUMENT - Karapetyan, Mariam (Foreign Languages for Special Purposes, 2023)
Language is one of the primary instruments in the field of Law-therefore it is essential for the lawyers to harmonize the rules of general logic with the syntactic logic of the legal sentence. As is known, legal documents may have quite complex syntactic structures. An example of such a structure is the sales and purchase agreement in Armenian which is analysed in the present article from the syntactic, stylistic, logical and semiotic aspects.
Keywords: Legal document; jurisprudence; logical reasoning; gradation; semiotic point of view